A new framework for classifying mosque energy models - Abd Rahman, Nurul Asra; Kamaruzzaman, Syahrul Nizam; Akashah, Farid Wajdi; Mohmad Zainordin, Zainab; Alias, Zarina (UiTM Press, 2025)
Energy usage is significantly impacted by mosque designs, building envelops, and the use of various ventilation systems. Factors including geographic location, climate, and social and cultural origins have less significant impact on mosque architecture in Malaysia. Given Malaysia's tropical environment, social and cultural factors which might differ by region have a greater impact on mosque architecture than weather. Since Thematic Analysis (TA) is a comprehensive and successful approach in qualitative research, it has been used in this study to deepen our understanding of mosque classifications. In order to create a categorisation model for mosques, the study focuses on occupancy, design features, envelopes, and ventilation systems. Classifying mosques according to these attributes is crucial since they have an impact on energy use.